(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
There are more than 400 million people with diabetes in the world, and diabetes is a chronic disease related to metabolism, more specifically, insulin, and it is considered one of the non-infectious (non-communicable) diseases that have been increasing dramatically among the population in recent years. Over the past 25 years, the number of adults with diabetes has quadrupled. There are many misconceptions about this disease.